Dynamics of the Negotiation Process in the Efforts to Free the Susi Air Pilot Hostage in Papua - Rini Asriani; Wahyudi Gobel; Karlina Napu; Ely Ibrahim; Minarni Adam (Journal of Governance and Global Studies, 2025)
This article thoroughly examines the complex dynamics of the negotiation process that took place during the attempt to free Susi Air pilot Philips Max Martin, who was held hostage by the Armed Criminal Group (KKB) in Papua. This study aims to provide a comprehensive analysis of the various factors that influenced the success of the negotiation, as well as the important role of the government in this complex situation. Using a qualitative research methodology, this study draws on a variety of literature, including books, academic journals, and relevant articles that discuss the theme of negotiation and hostage situations in the unique socio-political context of Papua. The research findings reveal that the success of the negotiation was greatly influenced by effective communication strategies, a deep understanding of local cultural and social dynamics, and the active involvement of various stakeholders, including community leaders and government representatives. This article aims to provide valuable insights into the negotiation process in hostage situations, particularly in conflict-ridden areas, and to offer recommendations for future approaches to similar crises.